A second-generation vaccine protects against the psychoactive effects of cocaine - Carrera, M. Rocío A. (The National Academy of Sciences, 2001)
The effects of immunization with the second-generation cocaine immunoconjugate GND-keyhole limpet hemocyanin (KLH) or with the anti-cocaine mAb GNC92H2 were assessed in a model of acute cocaine-induced locomotor activity. After i.p. administration of cocaine⋅HCl (15 mg/kg), rats were tested in photocell cages, and stereotypy was rated to determine preimmunization drug response (baseline). Experimental animals were subjected to an immunization protocol with GND-KLH or treated with the mAb GNC92H2. Rats were then challenged with systemic cocaine, and their locomotor responses were again measured. Active immunization with GND-KLH produced a 76% decrease in the ambulatory measure (crossovers) in the experimental group and a 12% increase in the control group compared with baseline values. Also, stereotypic behavior was significantly suppressed in the vaccinated animals. Decreases in both measures were seen in the experimental group on two subsequent challenges. The maximum effect was observed at the time of the second challenge with a dramatic 80% decrease in crossovers. Treatment with GNC92H2 resulted in a 69% decrease in crossovers compared with baseline. This effect persisted across two additional challenges over 11 days with decreases of 46–47%. In contrast, the control group showed increases of up to 28%. Significant differences between groups were observed in the stereotypic measure in all three challenges. The results indicate that these immunopharmacotherapeutic agents have significant cocaine-blockade potential and therefore may offer an effective strategy for the treatment of cocaine abuse.